The Role of SR-BI in sepsis: leveraging mechanistic insights to advance precision steroid therapy - Guo, Ling; Wang, Qian; Li, Xiang-An (Frontiers in Immunology, 2025)
According to the Surviving Sepsis Campaign, 50.3% of septic shock patients received steroid/glucocorticoid (GC) therapy. However, whether GC therapy is beneficial and who might benefit from it are hotly debated. Initial guidelines recommended GC therapy for septic patients with adrenal insufficiency, but this has since been retracted. Recent studies using animal models of adrenal insufficiency have shed light on the mechanisms, demonstrating that the adrenal stress response is a part of the host response that is essential for control inflammatory response in sepsis and the adrenal insufficiency is a risk factor for sepsis. This perspective review explores the limitations of GC therapy through the lens of GC biology, with a particular focus on the role of scavenger receptor class B type I (SR-BI) in mediating the adrenal stress response. We highlight the mechanisms of how SR-BI-mediated adrenal stress response contributes to the regulation of hyperinflammation and innate immune responses. By integrating mechanistic insights with the limitations of GC therapy, we advocate for a precision medicine approach to GC therapy in sepsis– selectively applying GC therapy for patients with adrenal insufficiency, not without.